Agents of Change: How Immigrant-Run Ethnic Food Retailers Improve Food Environments. Issue 3 (3rd July 2017) - Khojasteh, Maryam; Raja, Samina
ABSTRACT: Immigrant-run ethnic food retail stores, which are often located in urban neighborhoods, are reported to provide healthy foods. Yet, there is little research on how these stores manage to operate successfully in low-resource environments, which are reported to have poor access to healthy foods, and the challenges they must overcome in a broken food system. Based on a qualitative pilot case study of Middle Eastern stores in Buffalo, New York, the authors report factors that enable immigrant entrepreneurs to operate healthy food retail stores in low-income urban neighborhoods and the challenges they must overcome in the process. Factors for success include store owners' membership in ethnic networks, prior business experience, and understanding of niche market opportunities. This article reports policy suggestions for how local governments can help ethnic food retailers to create healthier food environments and foster economic and community development.